Typha latifolia L. (Typhaceae), nuevo registro para la flora de Chile - URRUTIA, JONATHAN; MARTICORENA, ALICIA; SÁNCHEZ, PAULINA (Gayana Botánica, 2017)
For first time in Chile, is documented the presence of Typha latifolia L., a species that occurs mainly in wetlands, and up to date it was only registered in neighboring countries. This new species record was found in the Talcahuano area, Biobío Region. A morphological description of the plant is provided and also an identification key for the species of the Typha genus growing in Chile.